Qualitative Case Study on Virtual Simulations Engaging Educational Leadership Candidates in Ethical Scenarios that Positively Impacted Leadership Skills (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2024)
In this paper, the authors describe one leadership preparation program's approach to enhancing ethics and ethical decision-making by embedding high-impact practices and experiential learning opportunities for leadership candidates. The conceptual framework for this research was based on Kolb's Experiential Learning Theory (ELT) and Kuh's High-Impact Practices (HIPs) to connect theory and practice through practical feedback and leadership coaching. Using experiential virtual simulation experiences provided opportunities for Educational Leadership candidates to apply instructional and ethical leadership practices to authentic, problem-based situations in an innovative online educational leadership program. This approach allowed faculty to offer specific growth areas to strengthen and improve aspiring school leaders' ethical decision-making practices. Furthermore, the paper discusses how virtual simulation enhanced candidates' transformation learning process and bridge theory to practice in a virtual reality environment.